A inteligência competitiva organizacional e os sistemas integrados de gestão ERP: um estudo nas indústrias calçadistas de Jaú - Rodrigues, Rodrigo [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
In the world globalized the information have seen, extremely important role that to economy and requires excellence regarding the information and documentation systems, by that even the information became a resource of extremely important management, but do not always be valued correctly on the part of organizations. In organizational environments is absolutely necessary the utilization of technological resources for mediate the access and use of information by the user, as well like for support the distinct organizational activities, since the routine activities, the decision making process, until the planning of strategic actions. The focus of problem of research refers to the information flows in organizational scope, more specifically the information flows linked to the organizational competitive intelligence process (OCI). The objective of this study aims analyze the contribution of information and communication technologies (ICTs), through the management integrated systems, more specifically the Enterprise Resource Planning (ERP), applied to the organizational competitive intelligence process in the associated industries to the Footwear Syndicate of Jaú/SP city. Intends to study the concepts, definitions, approaches and techniques related to the OCI process and ICTs, more specifically the ERP, through the analysis the international and national literature, as well as intends identify and analyze in universe researched the industries that possess and apply the system ERP or another similar system, aiming at analyze the relation of the use of that system kind for the organizational competitiveness. Similarly, intends to verify the occurrence of use of approaches and techniques applied to the organizational competitive intelligence process, since based in ERP systems. The research is descriptive exploratory, of qualitative nature, analyzes data and information collected... (Complete abstract click electronic access below)

No mundo globalizado as informações têm papel extremamente importante, visto que a internacionalização da economia exige excelência em relação aos sistemas de informação e documentação, por isso mesmo as informações se tornaram um recurso de gestão extremamente importante, mas nem sempre são valorizadas corretamente por parte das organizações. Nos ambientes organizacionais é absolutamente necessária a utilização de recursos tecnológicos para mediar o acesso e uso da informação pelo usuário, bem como para apoiar as distintas atividades organizacionais, desde as atividades cotidianas, o processo decisório, até o planejamento de ações estratégicas. O foco do problema de pesquisa refere-se aos fluxos informacionais em âmbito organizacional, mais especificamente os fluxos informacionais vinculados ao processo de inteligência competitiva organizacional (ICO). O objetivo deste estudo visava a analisar a contribuição das tecnologias de informação e comunicação (TICs), através dos sistemas integrados de gestão, mais especificamente o Enterprise Resource Planning (ERP), aplicado ao processo de inteligência competitiva organizacional nas indústrias associadas ao Sindicato Calçadista da cidade de Jaú/SP. Estudou-se os conceitos, definições, métodos e técnicas relacionados ao processo de ICO e às TICs, mais especificamente o ERP, por meio da análise da literatura nacional e internacional, assim como identificou-se e analisou-se no universo pesquisado as indústrias que possuem e aplicam o sistema ERP ou outro sistema semelhante, visando a analisar a relação do uso desse tipo de sistema para a competitividade organizacional. Da mesma forma, verificou-se a ocorrência do uso de métodos e técnicas aplicados ao processo de inteligência competitiva organizacional, desde que baseados em sistemas ERP. A pesquisa é descritiva exploratória...
Keywords: Gestão do conhecimento; Sistemas de informação gerencial; Sistema Integrado de Gestão (SIG); Inteligência competitiva Organizacional (ICO); Tecnologias de informação e Comunicação; Organizational Competitive Intelligence (OCI); Information Systems; Management Integrated System (MIS); Information and Communication Technologies (ICTs); Enterprise Resource Planning (ERP)